Abstract Number ‐ 126: Use of Woven EndoBridge device for Aneurysms in Off‐Labeled Locations: Systematic Review and Meta‐Analysis - Aaron Rodriguez‐Calienes; Juan Vivanco‐Suarez; Milagros Galecio‐Castillo; Marco Malaga; Cynthia Zevallos; Mudassir Farooqui; Cristian Moran‐Mariños; Noel F. Fanning; Oktay Algin; Boris Pabon; Nikolaos Mouchtouris; Pascal Jabbour; et al. (Stroke: Vascular and Interventional Neurology, 2023)
Introduction The Woven EndoBridge (WEB) device was originally approved to treat intracranial wide‐necked saccular bifurcation aneurysms. Recent studies have suggested its use for the treatment of intracranial aneurysms (IA) in alternative locations with variable success. We aimed to evaluate the safety and efficacy of the WEB for IAs in off‐labeled locations using a meta‐analysis (MA) of the literature. Methods We performed a systematic review of all studies including patients treated with WEB for IAs in locations different than what is currently on‐label FDA until May 2022. Our primary efficacy and safety outcomes were adequate occlusion at last follow up and a composite of intraprocedural and postprocedural complications, respectively. The Raymond‐Roy (RR) scale and the Bicêtre Occlusion Scale Score (BOSS) were used to define complete (RR: 1; BOSS: 0‐0’) and adequate (RR:1‐2; BOSS: 0–2) occlusion. Additional safety outcomes included intraprocedural (thromboembolic, hemorrhagic, device deployment, or air embolism) and postprocedural (ischemic or hemorrhagic) complications, and mortality. We performed a random‐effects MA of proportions and assessed the certainty of the evidence using the GRADE approach. Statistical heterogeneity across studies was assessed with I2 statistics. Logistic regression of the patient level data was used to study the predictors of complete occlusion. Results Ten studies were selected, and 285 patients (79% female; mean age 58 years) with 288 aneurysms (35% ruptured) were included. Adequate and complete occlusion rates were 89% (95% CI 81–94%; I2 = 0%; moderate‐certainty evidence) and 64% (95% CI 57–70%; I2 = 13%; moderate‐certainty evidence), respectively. The composite safety outcome rate was 8% (95% CI 3–17%; I2 = 34%; very low‐certainty evidence). The intraprocedural and postprocedural complication rates were 6% (95% CI 4–10%; I2 = 0%; very low‐certainty evidence) and 1% (95% CI 0–1%; I2 = 33%; very low‐certainty evidence), respectively. The mortality rate was 2% (95% CI 1–7%; I2 = 0%; very low‐certainty evidence). Aneurysm width (OR = 0.5; p = 0.03) was the only significant predictor of complete occlusion. Conclusions The preliminary studies evaluating the use of WEB for the treatment of IAs in off‐labeled locations has demonstrated rates of adequate occlusion and procedural complications comparable to the landmark studies that evaluated the use of the WEB for on‐label bifurcation aneurysms. Given the level of evidence, we consider the interpretation of our results should be done cautiously until confirmation from larger prospective studies are obtained.